Chloride intracellular channel gene knockdown induces insect cell lines death and level increases of intracellular calcium ions - Song, Jiqiang; Yu, Yanping; Yan, Zhichao; Xiao, Shan; Zhao, Xianxin; Wang, Fang; Fang, Qi; Ye, Gongyin (Frontiers in Physiology, 2023)
Chloride intracellular channel (CLIC) is a member of the chloride channel protein family for which growing evidence supports a pivotal role in fundamental cellular events. However, the physiological function of CLIC in insects is still rarely uncovered. The ovary-derived High Five (Hi-5) cell line isolated from the cabbage looper (Trichoplusia ni) is widely used in laboratories. Here, we studied both characteristics and functions of CLIC in Hi-5 cells (TnCLIC). We identified the TnCLIC gene in Hi-5 cells and annotated highly conserved CLIC proteins in most insect species. After RNA interference of TnCLIC, the phenomenon of significantly increased cell death suggests that the TnCLIC protein is essential for the survival of Hi-5 cells. The same lethal effect was also observed in Spodoptera frugiperda 9 and Drosophila melanogaster Schneider 2 cells after CLIC knockdown. Furthermore, we found that this kind of cell death was accompanied by increases in intracellular calcium ions after TnCLIC knockdown with the transcriptomic analyses and the detection of calcium levels. Our results provide insights into insect CLIC as a key factor for cell survival and lay the foundation for the cell death mechanism.